Critical social theory of the Frankfurt school: between Marxism and psychoanalysis - Sidorenko, Irina N. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The article analyses the socio-critical theories of the Frankfurt school. The author of this article concludes that Marxism and psychoanalysis represent the main components of the criticism of T. L. W. Adorno, M. Horkheimer, and H. Marcuse. The author of this article revealed the main epistemological reference point of the Frankfurt school’s critical social theory. It is represented by the spectrum of research in the field of Marxist anthropology, combined with psychoanalytic theory and the concept of ideology, which, describing the general social tendency to escapism caused by instrumental and practical attitudes of knowledge, legitimises the escalation of social repression and forms the authoritarian nature of personality. The article reveals the methodological potential of the projects of synthesis of Marxism and psychoanalysis, carried out by representatives of the Frankfurt school, both in explaining the evolution of social destruction and the formation of the authoritarian type of personality, and in developing programs of social change.
Keywords: critical social theory; Frankfurt school; Marxism; neo-Marxism; psychoanalysis; cultural industry; authoritarian personality type; one-dimensional man; destruction; mass society